Adsorption performance of hydrophobically modified silica gel for the vapors of -hexane and water - Weiqiu Huang; Jixing Xu; Bo Tang; Hongning Wang; Xiaobin Tan; Aihua Lv (Adsorption Science & Technology)
An ordinary silica gel (SG-1) was chosen as the raw material and hydrophobically modified with trimethylchlorosilane under different microwave exposure. The orthogonal experiment was designed to screen the optimized modification method. The hydrophobic properties modified silica gel (SG-2) was analyzed by comparing the difference changes of surface chemistries. Then, the adsorption capacities of SG-1 and SG-2 to the n -hexane vapor and water vapor, respectively, were investigated and compared with the capacities of activated carbon and SG-3 (hydrophobically modified using the same composite modifier without microwave exposure). Meanwhile, there cyclable adsorptions of SG-2 to the two vapors were conducted while the desorptions of vacuum and heat was observed. The results showed that the effect of hydrophobic modification to SG-1 under microwave exposure was obvious and SG-2 also had a very good effect of adsorption for the n -hexane vapor. The modified silica gel shows great potential and effect for the recovery of volatile organic compounds with high content of water.